Xenosporium amomi sp. no v. from Zingiberaceae in Thailand - Bussaban B. (2014)
Xenosporium thaxteri and an undescribed species of Xenosporium were found as saprobes on dead pseudostems of Alpinia malaccensis and Amomum siamense in Doi Suthep-Pui National Park, Chiang Mai, Thailand. The new species, X. amomi is described, illustrated and compared with similar Xenosporium species. The diagnostic characters of the 14 accepted species of Xenosporium are provided and the genus is reviewed based on the literature.